Mitochondrial DNA from archived tissue samples kept in formalin for forensic odontology studies - Rahul Pandey; Divya Mehrotra; Pradnya Kowtal; Abbas Ali Mahdi; Rajiv Sarin (Journal of Oral Biology and Craniofacial Research)
Background: Samples used for DNA isolation to be used for forensic odontology studies are often limited. The possibility to use tissue samples stored in formalin for a prolonged period, which contains nucleic acids of questionable quality, opens exciting possibilities for genetic and molecular biology studies useful in speciality of forensic odontology. Aim: The present study defines substantial modification of existing protocols for total genomic isolation including mitochondrial DNA and proves the utility of such obtained mitochondrial DNA in microsatellite analyses. Methods: 50 dental tissue samples which were kept in neutral buffered formalin liquid bottles were taken for DNA isolation and subsequent analysis. For the isolation of total genomic DNA from tissue samples, a new protocol with substantial modifications from routine ones was adopted by us. Total genomic DNA from matched blood samples were extracted using standard phenol-chloroform extraction method. Results: Polymerase Chain Reaction and Sequencing of such extracted DNA samples for mitochondrial D loop region were successful and the results were comparable with DNA extracted from normal sources of samples. Conclusion: The present study reports for the first time that nucleic acids extracted from human dental tissue samples under prolonged formalin fixation times can be used for forensic odontology studies using the described methodology.